Men's Sheds function and philosophy: Towards a framework for future research and men's health promotion - Wilson, N.; Cordier, Reinie; Doma, K.; Misan, G.; Vaz, Sharmila (Australian Health Promotion Association, 2015)
© 2015 Australian Health Promotion Association. Issue addressed The Men's Shed movement supports a range of men's health promotion initiatives. This paper examines whether a Men's Shed typology could inform future research and enable more efficient and targeted health promotion activities through Men's Sheds. Methods The International Men's Shed Survey consisted of a cross-sectional exploration of sheds, their members, and health and social activities. Survey data about shed 'function' and 'philosophy' were analysed using descriptive and inferential statistics. Results A framework of Men's Sheds based on function and philosophy demonstrated that most sheds serve a primary utility function, a secondary social function, but most importantly a primary social opportunity philosophy. Sheds with a primary health philosophy participated in fewer health promotion activities when compared with sheds without a primary health philosophy. Conclusions In addition to the uniform health promotion resources distributed by the Men's Shed associations, specific health promotion activities, such as prostate education, are being initiated from an individual shed level. This framework can potentially be used to enable future research and health promotion activities to be more efficiently and effectively targeted. So what? Men experience poorer health and well being outcomes than women. This framework offers a novel approach to providing targeted health promotion activities to men in an environment where it is okay to talk about men's health.